إشكالية ترجمة أسلوب النداء في القرآن الكريم في كتاب " فتح الحميد " الشيخ محمد خان الشيخ محمد خان الجالندهري نماذج مختارة – دراسة تحليلية نقدية: The problem of translating the method of the call in the Holy Qur’an in the book “Fath Al Hamid” by Sheikh Muhammad Khan Al Jalandhari - Mona Handacaha Ahmed Mahmood (MEI, 2023)
The problem of translating the method of the call in the Holy Qur’an in the book “Fath Al Hamid” by Sheikh Muhammad Khan Al Jalandhari Selected models An introduction The call is vastly used in the Holy Qur’an, and it is distinguished among other methods of discourse that it has a deep impact that touches human feelings, and provokes mental thoughts, as it directs the addressee to what benefits him, fixes his conditions in both homes, and socializes him near the caller. It also varies in line with the situation of the addressees and their response. The aspects of the discourses in the Holy Qur’an are general in which there is complete agreement with the place, and the case as well. Like any other translations, the Urdu translation of Qur’anic texts has received a great deal of controversy by researchers, as they found errors in them that are characterized by increase and decrease in meaning. Hence, it was necessary to study these translations and compare their connotations with the original text in order to reach a sound approach in translating the Qur’anic text. Therefore, this research paper came to find out how to translate the methods of the call in the Holy Qur’an, and translate it into Urdu through one of the most famous translations that appeared in the twentieth century. The book “Fath Al Hamid” by Mawlawi Fath Muhammad Jalandhari, which was printed in 1900. It was printed again under the name “Nur al-Hedaya” in 1969 so as to identify the translation problem so that translators could deal with the call method in the Holy Qur’an and the requirements of its translation, by linking the grammatical and rhetorical study to the analytical study trying to provide reasons and interpretations as possible through models from Quranic verses.